Indoor exposure to particles emitted by biomass-burning heating systems and evaluation of dose and lung cancer risk received by population. (April 2018) - Stabile, L.; Buonanno, G.; Avino, P.; Frattolillo, A.; Guerriero, E.
Abstract: Homes represent a critical microenvironment in terms of air quality due to the proximity to main particle sources and the lack of proper ventilation systems. Biomass-fed heating systems are still extensively used worldwide, then likely emitting a significant amount of particles in indoor environments. Nonetheless, research on biomass emissions are limited to their effects on outdoor air quality then not properly investigating the emission in indoor environments. To this purpose, the present paper aims to evaluate the exposure to different airborne particle metrics (including both sub- and super-micron particles) and attached carcinogenic compounds in dwellings where three different heating systems were used: open fireplaces, closed fireplaces and pellet stoves. Measurements in terms of particle number, lung-deposited surface area, and PM fraction concentrations were measured during the biomass combustion activities, moreover, PM10 samples were collected and chemically analyzed to obtain mass fractions of carcinogenic compounds attached onto particles. Airborne particle doses received by people exposed in such environments were evaluated as well as their excess lung cancer risk. Most probable surface area extra-doses received by people exposed to open fireplaces on hourly basis (56 mm 2  h −1 ) resulted one order of magnitude larger than those experienced for exposure to closed fireplaces and pellet stoves. Lifetime extra risk of Italian people exposed to the heating systems under investigation were larger than the acceptable lifetime risk (10 −5 ): in particular, the risk due to the open fireplace (8.8 × 10 −3 ) was non-negligible when compared to the overall lung cancer risk of typical Italian population. Graphical abstract: Image 1 Highlights: Evaluation of exposure to airborne particles emitted by heating systems in indoors. Chemical characterization of the particles emitted by wood and pellet combustion. Evaluation of the dose and lung cancer risk received by people exposed. High exposure levels, doses and risks related to wood combustion in open fireplaces. Abstract : The exposure, dose and risk of people due to airborne particles emitted by different biomass-burning heating systems in indoor environments were assessed. A high exposure (and then dose and risk) to open fireplaces was recognized.